Sustainability of Rural Nonprofit Organizations: Czech Republic and Beyond - Vladislav Valentinov; Gabriela Vaceková (Sustainability, 2015)
Sustainability of nonprofit organizations is a key concern for today's nonprofit scholars and practitioners. Building upon the nonprofit economics literature, the present paper introduces the distinction between the demand-side and supply-side determinants of nonprofit sustainability and makes the case for the discrepancy between them. This discrepancy presents not only a generic conceptual explanation of the nonprofit sustainability problems but is also applicable to the context of the European rural nonprofit sector. Three arguments are advanced. First, the notorious implementation problems of LEADER partnerships can be explained as a manifestation of the above discrepancy. Second, and related, the rural context implies the tendency of the supply-side determinants of nonprofit sustainability to undermine the demand-side ones. Third, recent empirical findings from the Czech Republic show that this tendency does not necessarily imply the possibility of a clear classification of the demand-side and supply-side sustainability determinants. Rather, those features of rural areas and communities that significantly affect the size of the local nonprofit sector exhibit a controversial entanglement of demand-side and supply-side identities.
Keywords: 330; nonprofit organizations; nonprofit economics; rural development; rural partnerships; Czech Republic